A Study of Three Publicly Listed Saas Companies Viewed through the Disruptive Innovation Framework - Birrell, Christopher Charles (2007)
The enterprise software industry has been dominated by several large firms such as Microsoft,Oracle, IBM, SAP and TCS over the past two decades. Very few examples of new large new firms have been able to erode market share from these large incumbent firms. The aim of this study is to show that new Software as a Service (SaaS) firms are disruptive to incumbents in the enterprise software market. By using Christensen’s theory of disruptive innovation and through the detailed analysis of published annual reports, three SaaS firms, RightNow Technologies, Salesforce.com and WebEx, are tested. Christensen’s disruptive innovation theory provides a set of litmus tests that enable a thorough ex post examination of the ability of these three firms to practice disruption. A set of tests, some business model related, some financial, are carried out and for each firm and a score of disruptiveness is assigned. The results of these tests indicate that SaaS is indeed disruptive. By following a vertically integrated strategy, lowering transaction costs and reducing agency risks, SaaS firms are providing Chief Information Officers (CIOs) with alternative best of breed enterprise solutions. Customers are passed on the savings through better coordination of the IT value chain and savings through shared infrastructure and multi-tenant server architectures. At the same time, SaaS firms are building wealth for their shareholders, and all this bears well for future emergence of new SaaS firms. The affects of the open source software (OSS) community and software standards bodies on SaaS is discussed; these are positive influences on the disruptiveness of SaaS.